A INSERÇÃO DA GINÁSTICA ORIENTAL LIEN CH`I NA EDUCAÇÃO FÍSICA ESCOLAR - Leandro Alves da Cunha; Helena Faria de Barros (Universidade do Oeste Paulista, 2012)
The present study evaluated the technique of insertion eastern Lien Ch`i gymnastic as programmatic content from Physical Education discipline in schools of basic education, through the discipline teachers' view. The schools and the teachers belong to the public teaching service of São Paulo state, in the cities of Presidente Prudente-SP and Araçatuba-SP. The Education Department of São Paulo (SEE / SP) carried out such an intervention enabling its faculty in 2003 and 2004, effecting the practice of Lien Ch`i during the years 2005, 2006 and 2007. The current National Curricular Parameters (PCN's) suggest splitting the content of physical education in three blocks, a) sports, games, wrestling and gymnastics, b) Rhythmic and expressive Activities, c) knowledge about the body. Due to its rich job options, the Lien Ch`i may be inserted into any of the three blocks mentioned above. Added to these aspects, our interest was keen to investigate the characteristics of this modality and its effectiveness, motivation and acceptance of the people involved in the process. This research is predominantly qualitative, which most significant features are descriptive and interpretive content. Data were collected through an interview transcribed later and documents consultation. The studied teachers (n = 21) have demonstrated knowledge about the received training (Lien Ch `i) towards to origin and history, constitution, composition and goals of the exercises, as well as its help to maximize schoolchildren learning. The teachers were direct agents in the implementation and development of the proposal which took place in state schools of São Paulo. It was observed greater reciprocity, acceptance and participation for Lien Ch`i, as well as better use of lessons in the first cycle of primary education (1st to 4th grades). It was detected a strong dissatisfaction over the proposed curriculum content inserted in the discipline of Physical Education (69.3%) and an even greater dissatisfaction about the non continuation of these proposals (85.7%). The main factors listed for this dissatisfaction were: the imposition of arbitrary and disrespectful public education policies, the non continuation of the "insertions" with government changes or in the same government with a different education secretary